2004
DOI: 10.1111/j.1365-2125.2005.02231.x
|View full text |Cite
|
Sign up to set email alerts
|

National Prescribing Service: creating an implementation arm for national medicines policy

Abstract: Medicines make an essential contribution to the health of the community, but rapidly rising drug budgets have caused governments to seek ways of ensuring this expenditure results in value for money. The National Prescribing Service was established against this background to implement a quality use of medicines service as par t of the National Medicines Policy. A range of programmes that attempt to use evidencebased strategies to deliver evidence-based messages have been established. These use multifaceted inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 15 publications
0
26
0
3
Order By: Relevance
“…23 The HMR service represents a key component of Australia's National Medicines Policy for achieving the quality use of medicines and comprises the following steps: (1) the GP refers the patient to the patient's preferred community pharmacy, based on standard criteria (eg, the patient is taking ≥5 medicines or a medicine with narrow therapeutic index); (2) the pharmacist conducts an interview, usually in the patient's home, to obtain a comprehensive medication profile; (3) the pharmacist prepares a written report documenting HMR findings and recommendations that is sent to the GP; and (4) the GP and patient agree on a medication management plan based on the HMR report. 24, 25 The main aim of this study was to retrospectively evaluate the impact of HMRs on the appropriateness of prescribing, using the MAI as a tool to categorize pharmacists' recommendations. The specific objectives were to evaluate the overall impact of recommendations made by pharmacists on the appropriateness of prescribing; to evaluate the impact of recommendations made by each individual pharmacist; and to evaluate the impact of HMRs on prescribing appropriateness after uptake of pharmacist recommendations by GPs.…”
mentioning
confidence: 99%
“…23 The HMR service represents a key component of Australia's National Medicines Policy for achieving the quality use of medicines and comprises the following steps: (1) the GP refers the patient to the patient's preferred community pharmacy, based on standard criteria (eg, the patient is taking ≥5 medicines or a medicine with narrow therapeutic index); (2) the pharmacist conducts an interview, usually in the patient's home, to obtain a comprehensive medication profile; (3) the pharmacist prepares a written report documenting HMR findings and recommendations that is sent to the GP; and (4) the GP and patient agree on a medication management plan based on the HMR report. 24, 25 The main aim of this study was to retrospectively evaluate the impact of HMRs on the appropriateness of prescribing, using the MAI as a tool to categorize pharmacists' recommendations. The specific objectives were to evaluate the overall impact of recommendations made by pharmacists on the appropriateness of prescribing; to evaluate the impact of recommendations made by each individual pharmacist; and to evaluate the impact of HMRs on prescribing appropriateness after uptake of pharmacist recommendations by GPs.…”
mentioning
confidence: 99%
“…The HMR service represents a key component of Australia's National Medicines Policy for achieving the quality use of medicines and comprises the following steps: (a) General practitioner (GP) referral of the patient to the patient's preferred community pharmacy based on standard criteria, for example: patient is taking five or more medicines or a medicine with narrow therapeutic index; (b) Pharmacist conducts an interview usually in the patient's home, to obtain a comprehensive medication profile; (c) Pharmacist prepares a written report documenting HMR findings and recommendations and is sent to the GP; and (d) GP and the patient agree on a medication management plan based on the HMR report (Department of Health and Ageing, 2001;Weekes, Mackson, Fitzgerald, & Phillips, 2005). Although medication review programs have been shown to be effective in optimizing the prescribing for older people (Castelino et al, 2009;Castelino, Hilmer, Bajorek, Nishtala, & Chen, 2010), much of this focus has been toward reducing the overuse or misuse of medications, whereas their impact on the use of frequently omitted drug therapies has been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…It targets areas where medication use may be associated with suboptimal health outcomes or increased costs 14. In 2009–2010, NPS MedicineWise implemented the multifaceted nationwide Stroke Prevention Program in Australia.…”
Section: Introductionmentioning
confidence: 99%